Orbits of M Dwarf Binaries Big and Small: Revealing Their Sizes and Shapes Via a Multi-Pronged Observing Campaign - Vrijmoet, Eliot; Henry, Todd; Tokovinin, Andrei; Dieterich, Serge; Horch, Elliott; Jao, Wei-Chun; Winters, Jennifer; Team, Recons (Bulletin of the American Astronomical Society, 2022)
Presentation #205.10 in the session Binary Stellar System - iPoster Session.
Keywords: dept.phy; ⛔ No DOI found

The RKSTAR Concert — A RECONS Survey of the 5000 Nearest K Dwarfs - Henry, Todd; Casetti-Dinescu, Dana; Horch, Elliott; Hubbard-James, Hodari-Sadiki; Jao, Wei-Chun; Lesley, D. Xavier; Paredes, Leonardo; Shea, Melissa; Sutherland, Torrie; Team, Recons (Bulletin of the American Astronomical Society, 2022)
Presentation #305.15 in the session Stars, Cool Dwarfs, Brown Dwarfs — iPoster Session.
Keywords: dept.phy; ⛔ No DOI found

Preface - Jain, F.; Broadbridge, C.; Gherasimova, M.; Tang, H. (Nanostructures For Electronics, Photonics, Biosensors, And Emerging Systems Applications, 2022)
0 citations (Crossref) [2023-10-31] ISBN: 9789811270796
Keywords: dept.phy

Waste Citrus reticulata Assisted Preparation of Cobalt Oxide Nanoparticles for Supercapacitors - Srivastava, Rishabh; Bhardwaj, Shiva; Kumar, Anuj; Singhal, Rahul; Scanley, Jules; Broadbridge, Christine C.; Gupta, Ram K. (Nanomaterials, 2022)
The green, sustainable, and inexpensive creation of novel materials, primarily nanoparticles, with effective energy-storing properties, is key to addressing both the rising demand for energy storage and the mounting environmental concerns throughout the world. Here, an orange peel extract is used to make cobalt oxide nanoparticles from cobalt nitrate hexahydrate. The orange peel extract has Citrus reticulata, which is a key biological component that acts as a ligand and a reducing agent during the formation of nanoparticles. Additionally, the same nanoparticles were also obtained from various precursors for phase and electrochemical behavior comparisons. The prepared Co-nanoparticles were also sulfurized and phosphorized to enhance the electrochemical properties. The synthesized samples were characterized using scanning electron microscopic and X-ray diffraction techniques. The cobalt oxide nanoparticle showed a specific capacitance of 90 F/g at 1 A/g, whereas the cobalt sulfide and phosphide samples delivered an improved specific capacitance of 98 F/g and 185 F/g at 1 A/g. The phosphide-based nanoparticles offer more than 85% capacitance retention after 5000 cycles. This study offers a green strategy to prepare nanostructured materials for energy applications.
3 citations (Crossref) [2023-10-31] Number: 23
Keywords: Citrus reticulata; Co_3O_4 nanoparticles; characterization; charge storage; dept.phy; peer-reviewed; supercapacitors

Chapter 15 - Tryptophan fluorescence and machine learning to study the aggressiveness of prostate cancer cell lines: A pilot study - Xue, Jianpeng; Mo, Haiding; Tian, Yuke; Tang, Rui; Wu, Binlin (Biophotonics, Tryptophan and Disease, 2022)
We report on the use of label-free, native fluorescence (NFL) spectroscopy and machine learning (ML) algorithms to study the correlation of relative tryptophan levels with prostate cancer aggressiveness. Three extensively studied prostate cancer cell lines were used; PC3, an aggressive, androgen-resistant line, with a high tendency to metastasize in vivo, DU-145, a less aggressive cancer cell line, also androgen-resistant, and LNCaP, an androgen sensitive line, which has a low tendency to metastasize. Using an excitation of 300nm, differences in the NFL spectral profiles from these cell lines were found to correlate with changes in the relative concentrations of tryptophan and reduced nicotinamide adenine dinucleotide (NADH). The use of ML may present a powerful tool for the assessment of the likelihood of a cancer to metastasize. This technique could aid in the decision whether to use highly aggressive adjuvant chemotherapy or radiation therapy after surgical resection of a prostate cancer.
Keywords: Fluorescence spectroscopy; Machine learning; Metastatic cancer; Native fluorescence; Prostate cancer; Support vector machine; Tryptophan; dept.phy

The Solar Neighborhood L: Spectroscopic Discovery of K Dwarfs Younger Than 1 Gyr and New Binaries within 30 pc - Hubbard-James, Hodari-Sadiki; Lesley, D. Xavier; Henry, Todd J.; Paredes, Leonardo A.; Nisak, Azmain H. (The Astronomical Journal, 2022)
As part of a comprehensive effort to characterize the nearest stars, the CHIRON echelle spectrograph on the CTIO/SMARTS 1.5 m telescope is being used to acquire high-resolution (R = 80,000) spectra of K dwarfs within 50 pc. This paper provides spectral details about 35 K dwarfs from five benchmark sets with estimated ages spanning 20 Myr–5.7 Gyr. Four spectral age and activity indicators are tested, three of which aligned with the estimated ages of the benchmark groups—the Na i doublet (5889.95 and 5895.92 Å), the Hα line (6562.8 Å), and the Li i resonance line (6707.8 Å). The benchmark stars are then used to evaluate seven field K dwarfs exhibiting variable radial velocities for which initial CHIRON data did not show obvious companions. Two of these stars are estimated to be younger than 700 Myr, while one exhibits stellar activity unusual for older K-dwarf field stars and is possibly young. The four remaining stars turn out to be spectroscopic binaries, two of which are being reported here for the first time with orbital periods found using CHIRON data. Spectral analysis of the combined sample of 42 benchmark and variable radial velocity stars indicates temperatures ranging from 3900 to 5300 K and metallicities from −0.4 < [Fe/H] < +0.2. We also determine for main-sequence K dwarfs. Ultimately, this study will target several thousand of the nearest K dwarfs and provide results that will serve present and future studies of stellar astrophysics and exoplanet habitability.
0 citations (Crossref) [2023-10-31]
Keywords: dept.phy; peer-reviewed

Measurement of HΛ4 and HeΛ4 binding energy in Au+Au collisions at sNN = 3 GeV - STAR Collaboration (Physics Letters B, 2022)
Measurements of mass and Λ binding energy of Λ4H and Λ4He in Au+Au collisions at sNN=3 GeV are presented, with an aim to address the charge symmetry breaking (CSB) problem in hypernuclei systems with atomic number A = 4. The Λ binding energies are measured to be 2.22±0.06(stat.)±0.14(syst.) MeV and 2.38±0.13(stat.)±0.12(syst.) MeV for Λ4H and Λ4He, respectively. The measured Λ binding-energy difference is 0.16±0.14(stat.)±0.10(syst.) MeV for ground states. Combined with the γ-ray transition energies, the binding-energy difference for excited states is −0.16±0.14(stat.)±0.10(syst.) MeV, which is negative and comparable to the value of the ground states within uncertainties. These new measurements on the Λ binding-energy difference in A = 4 hypernuclei systems are consistent with the theoretical calculations that result in ΔBΛ4(1exc+)≈−ΔBΛ4(0g.s.+)<0 and present a new method for the study of CSB effect using relativistic heavy-ion collisions.
2 citations (Crossref) [2023-10-31]
Keywords: dept.phy; peer-reviewed

Resolving the Core of R136 in the Optical - Kalari, V.M.; Horch, E.P.; Salinas, R.; Vink, J.S.; Andersen, M.; Bestenlehner, J.M.; Rubio, M. (Astrophysical Journal, 2022)
The sharpest optical images of the R136 cluster in the Large Magellanic Cloud are presented, allowing us for the first time to resolve members of the central core, including R136a1, the most-massive star known. These data were taken using the Gemini speckle imager Zorro in medium-band filters with effective wavelengths similar to BVRI achieving angular resolutions between 30-40 mas. All stars previously known in the literature, having V < 16 mag within the central 2″ × 2″, were recovered. Visual companions (≥40 mas; 2000 au) were detected for the WN5h stars R136 a1 and a3. Photometry of the visual companion of a1 suggests it is of mid-O spectral type. Based on new photometric luminosities using the resolved Zorro imaging, the masses of the individual WN5h stars are estimated to be between 150 and 200 M ⊙, lowering significantly the present-day masses of some of the most-massive stars known. These mass estimates are critical anchor points for establishing the stellar upper-mass function. © 2022. The Author(s). Published by the American Astronomical Society.
10 citations (Crossref) [2023-10-31]
Keywords: dept.phy; peer-reviewed

Centrality and transverse-momentum dependence of higher-order flow harmonics of identified hadrons in Au+Au collisions at sNN =200 GeV - STAR Collaboration (Physical Review C, 2022)
We present high-precision measurements of elliptic, triangular, and quadrangular flow v2, v3, and v4, respectively, at midrapidity for identified hadrons π, p, K, φ, Ks, Λ as a function of centrality and transverse momentum in Au+Au collisions at the center-of-mass energy sNN=200 GeV. We observe similar vn trends between light and strange mesons which indicates that the heavier strange quarks flow as strongly as the lighter up and down quarks. The number-of-constituent-quark scaling for v2, v3, and v4 is found to hold within statistical uncertainty for 0-10%, 10-40%, and 40-80% collision centrality intervals. The results are compared to several viscous hydrodynamic calculations with varying initial conditions, and could serve as an additional constraint to the development of hydrodynamic models. © 2022 American Physical Society.
6 citations (Crossref) [2023-10-31]
Keywords: dept.phy; peer-reviewed

The POKEMON Speckle Survey of Nearby M Dwarfs. I. New Discoveries - Clark, C.A.; Van Belle, G.T.; Horch, E.P.; Von Braun, K.; Ciardi, D.R.; Winters, J.G.; Kiman, R. (Astronomical Journal, 2022)
M dwarfs are favorable targets for exoplanet detection with current instrumentation, but stellar companions can induce false positives and inhibit planet characterization. Knowledge of stellar companions is also critical to our understanding of how binary stars form and evolve. We have therefore conducted a survey of stellar companions around nearby M dwarfs, and here we present our new discoveries. Using the Differential Speckle Survey Instrument at the 4.3 m Lowell Discovery Telescope, and the similar NN-EXPLORE Exoplanet Stellar Speckle Imager at the 3.5 m WIYN telescope, we carried out a volume-limited survey of M-dwarf multiplicity to 15 parsecs, with a special emphasis on including the later M dwarfs that were overlooked in previous surveys. Additional brighter targets at larger distances were included for a total sample size of 1070 M dwarfs. Observations of these 1070 targets revealed 26 new companions; 22 of these systems were previously thought to be single. If all new discoveries are confirmed, then the number of known multiples in the sample will increase by 7.6%. Using our observed properties, as well as the parallaxes and 2MASS K magnitudes for these objects, we calculate the projected separation, and estimate the mass ratio and component spectral types, for these systems. We report the discovery of a new M-dwarf companion to the white dwarf Wolf 672 A, which hosts a known M-dwarf companion as well, making the system trinary. We also examine the possibility that the new companion to 2MASS J13092185-2330350 is a brown dwarf. Finally, we discuss initial insights from the POKEMON survey. © 2022. The Author(s). Published by the American Astronomical Society.
4 citations (Crossref) [2023-10-31]
Keywords: dept.phy; peer-reviewed

Probing strangeness canonical ensemble with K−, ϕ(1020) and Ξ− production in Au+Au collisions at sNN=3 GeV - STAR Collaboration (Physics Letters B, 2022)
We report the first multi-differential measurements of strange hadrons of K−, ϕ and Ξ− yields as well as the ratios of ϕ/K− and ϕ/Ξ− in Au+Au collisions at sNN=3 GeV with the STAR experiment fixed target configuration at RHIC. The ϕ mesons and Ξ− hyperons are measured through hadronic decay channels, ϕ→K+K− and Ξ−→Λπ−. Collision centrality and rapidity dependence of the transverse momentum spectra for these strange hadrons are presented. The 4π yields and ratios are compared to thermal model and hadronic transport model predictions. At this collision energy, thermal model with grand canonical ensemble (GCE) under-predicts the ϕ/K− and ϕ/Ξ− ratios while the result of canonical ensemble (CE) calculations reproduce ϕ/K−, with the correlation length rc∼2.7 fm, and ϕ/Ξ−, rc∼4.2 fm, for the 0-10% central collisions. Hadronic transport models including high mass resonance decays could also describe the ratios. While thermal calculations with GCE work well for strangeness production in high energy collisions, the change to CE at 3 GeV implies a rather different medium property at high baryon density.
10 citations (Crossref) [2023-10-31]
Keywords: dept.phy; peer-reviewed

Probing the Gluonic Structure of the Deuteron with J/ψ Photoproduction in d+Au Ultraperipheral Collisions - STAR Collaboration (Physical Review Letters, 2022)
Understanding gluon density distributions and how they are modified in nuclei are among the most important goals in nuclear physics. In recent years, diffractive vector meson production measured in ultraperipheral collisions (UPCs) at heavy-ion colliders has provided a new tool for probing the gluon density. In this Letter, we report the first measurement of J/ψ photoproduction off the deuteron in UPCs at the center-of-mass energy sNN=200 GeV in d+Au collisions. The differential cross section as a function of momentum transfer -t is measured. In addition, data with a neutron tagged in the deuteron-going zero-degree calorimeter is investigated for the first time, which is found to be consistent with the expectation of incoherent diffractive scattering at low momentum transfer. Theoretical predictions based on the color glass condensate saturation model and the leading twist approximation nuclear shadowing model are compared with the data quantitatively. A better agreement with the saturation model has been observed. With the current measurement, the results are found to be directly sensitive to the gluon density distribution of the deuteron and the deuteron breakup process, which provides insights into the nuclear gluonic structure. © 2022 American Physical Society.
6 citations (Crossref) [2023-10-31]
Keywords: dept.phy; peer-reviewed

The Solar Neighborhood. XLIX. New Discoveries and Orbits of M-dwarf Multiples with Speckle Interferometry at SOAR - Vrijmoet, E.H.; Tokovinin, A.; Henry, T.J.; Winters, J.G.; Horch, E.; Jao, W.-C. (Astronomical Journal, 2022)
We present the first results of a multiyear program to map the orbits of M-dwarf multiples within 25 pc. The observations were conducted primarily during 2019-2020 using speckle interferometry at the Southern Astrophysical Research Telescope in Chile, using the High-Resolution Camera mounted on the adaptive optics module (HRCam+SAM). The sample of nearby M dwarfs is drawn from three sources: multiples from the RECONS long-term astrometric monitoring program at the SMARTS 0.9 m; known multiples, for which these new observations will enable or improve orbit fits; and candidate multiples flagged by their astrometric fits in Gaia Data Release 2 (DR2). We surveyed 333 of our 338 M dwarfs via 830 speckle observations, detecting companions for 63% of the stars. Most notably, this includes new companions for 76% of the subset selected from Gaia DR2. In all, we report the first direct detections of 97 new stellar companions to the observed M dwarfs. Here we present the properties of those detections, the limits of each nondetection, and five orbits with periods 0.67-29 yr already observed as part of this program. Companions detected have projected separations of 0.″024-2.″0 (0.25-66 au) from their primaries and have ΔI ≲ 5.0 mag. This multiyear campaign will ultimately map complete orbits for nearby M dwarfs with periods up to 3 yr, and provide key epochs to stretch orbital determinations for binaries to 30 yr. © 2022. The Author(s). Published by the American Astronomical Society.
8 citations (Crossref) [2023-10-31]
Keywords: dept.phy; peer-reviewed

A new absolute proper motion determination of leo i using HST/WFPC2 images and gaia EDR3 - Casetti-Dinescu, D.I.; Hansen, C.K.; Girard, T.M.; Kozhurina-Platais, V.; Platais, I.; Horch, E.P. (Astronomical Journal, 2022)
We measure the absolute proper motion of Leo I using a WFPC2/HST data set that spans up to 10 yr to date the longest time baseline utilized for this satellite. The measurement relies on ∼2300 Leo I stars located near the center of light of the galaxy; the correction to absolute proper motion is based on 174 Gaia EDR3 stars and 10 galaxies. Having generated highly precise, relative proper motions for all Gaia EDR3 stars in our WFPC2 field of study, our correction to the absolute EDR3 system does not rely on these Gaia stars being Leo I members. This new determination also benefits from a recently improved astrometric calibration of WFPC2. The resulting proper-motion value, (μ α , μ δ ) = (-0.007 0.035, - 0.119 0.026) mas yr-1 is in agreement with recent, large-area, Gaia EDR3-based determinations. We discuss all the recent measurements of Leo I's proper motion and adopt a combined, multistudy average of (μ α 3 meas,μ δ 3 meas)=(-0.036±0.016,-0.130±0.010) mas yr-1. This value of absolute proper motion for Leo I indicates its orbital pole is well aligned with that of the vast polar structure, defined by the majority of the brightest dwarf spheroidal satellites of the Milky Way. © 2021. The Author(s). Published by the American Astronomical Society.
3 citations (Crossref) [2023-10-31] tex.art_number: 1 tex.document_type: Article tex.source: Scopus
Keywords: dept.phy; peer-reviewed

Validation of 13 hot and potentially terrestrial TESS planets - Giacalone, S.; Dressing, C.D.; Hedges, C.; Kostov, V.B.; Collins, K.A.; Jensen, E.L.N.; Yahalomi, D.A.; Bieryla, A.; Ciardi, D.R.; Howell, S.B.; Lillo-Box, J.; Barkaoui, K.; et al. (Astronomical Journal, 2022)
The James Webb Space Telescope will be able to probe the atmospheres and surface properties of hot, terrestrial planets via emission spectroscopy. We identify 18 potentially terrestrial planet candidates detected by the Transiting Exoplanet Survey Satellite (TESS) that would make ideal targets for these observations. These planet candidates cover a broad range of planet radii (R p ∼0.6-2.0R ) and orbit stars of various magnitudes (K s = 5.78-10.78, V = 8.4-15.69) and effective temperatures (T eff ∼3000-6000 K). We use ground-based observations collected through the TESS Follow-up Observing Program (TFOP) and two vetting tools - DAVE and TRICERATOPS - to assess the reliabilities of these candidates as planets. We validate 13 planets: TOI-206 b, TOI-500 b, TOI-544 b, TOI-833 b, TOI-1075 b, TOI-1411 b, TOI-1442 b, TOI-1693 b, TOI-1860 b, TOI-2260 b, TOI-2411 b, TOI-2427 b, and TOI-2445 b. Seven of these planets (TOI-206 b, TOI-500 b, TOI-1075 b, TOI-1442 b, TOI-2260 b, TOI-2411 b, and TOI-2445 b) are ultra-short-period planets. TOI-1860 is the youngest (133 ± 26 Myr) solar twin with a known planet to date. TOI-2260 is a young (321 ± 96 Myr) G dwarf that is among the most metal-rich ([Fe/H] = 0.22 ± 0.06 dex) stars to host an ultra-short-period planet. With an estimated equilibrium temperature of 1/42600 K, TOI-2260 b is also the fourth hottest known planet with R p ¡ 2 R . © 2022. The Author(s). Published by the American Astronomical Society.
tex.art_number: 99 tex.document_type: Article tex.source: Scopus
Keywords: dept.phy; peer-reviewed

Observations with the Southern Connecticut Stellar Interferometer. I. Instrument Description and First Results - Horch, E.P.; Weiss, S.A.; Klaucke, P.M.; Pellegrino, R.A.; Rupert, J.D. (Astronomical Journal, 2022)
We discuss the design, construction, and operation of a new intensity interferometer, based on the campus of Southern Connecticut State University in New Haven, Connecticut. While this paper will focus on observations taken with an original two-telescope configuration, the current instrumentation consists of three portable 0.6 m Dobsonian telescopes with single-photon avalanche diode detectors located at the Newtonian focus of each telescope. Photons detected at each station are time stamped and read out with timing correlators that can give cross-correlations in timing to a precision of 48 ps. We detail our observations to date with the system, which has now been successfully used at our university in 16 nights of observing. Components of the instrument were also deployed on one occasion at Lowell Observatory, where the Perkins and Hall telescopes were made to function as an intensity interferometer. We characterize the performance of the instrument in detail. In total, the observations indicate the detection of a correlation peak at the level of 6.76σ when observing unresolved stars, and consistency with partial or no detection when observing at a baseline sufficient to resolve the star. Using these measurements, we conclude that the angular diameter of Arcturus is larger than 15 mas and that of Vega is between 0.8 and 17 mas. While the uncertainties are large at this point, both results are consistent with measures from amplitude-based long baseline optical interferometers. © 2022. The American Astronomical Society. All rights reserved.
4 citations (Crossref) [2023-10-31] tex.art_number: 92 tex.document_type: Article tex.source: Scopus
Keywords: dept.phy; peer-reviewed

Disappearance of partonic collectivity in sNN=3 GeV au+au collisions at RHIC - STAR Collaboration (Physics Letters, Section B: Nuclear, Elementary Particle and High-Energy Physics, 2022)
We report on the measurements of directed flow v1 and elliptic flow v2 for hadrons (π±, K±, KS0, p, ϕ, Λ and Ξ−) from Au+Au collisions at sNN=3 GeV and v2 for (π±, K±, p and p‾) at 27 and 54.4 GeV with the STAR experiment. While at the two higher energy midcentral collisions the number-of-constituent-quark (NCQ) scaling holds, at 3 GeV the v2 at midrapidity is negative for all hadrons and the NCQ scaling is absent. In addition, the v1 slopes at midrapidity for almost all observed hadrons are found to be positive, implying dominant repulsive baryonic interactions. The features of negative v2 and positive v1 slope at 3 GeV can be reproduced with a baryonic mean-field in transport model calculations. These results imply that the medium in such collisions is likely characterized by baryonic interactions. © 2022 The Author(s)
22 citations (Crossref) [2023-10-31] tex.art_number: 137003 tex.coden: PYLBA tex.document_type: Article tex.source: Scopus
Keywords: dept.phy; peer-reviewed

Light nuclei collectivity from sNN=3 GeV au+au collisions at RHIC - STAR Collaboration (Physics Letters, Section B: Nuclear, Elementary Particle and High-Energy Physics, 2022)
In high-energy heavy-ion collisions, partonic collectivity is evidenced by the constituent quark number scaling of elliptic flow anisotropy for identified hadrons. A breaking of this scaling and dominance of baryonic interactions is found for identified hadron collective flow measurements in sNN = 3 GeV Au+Au collisions. In this paper, we report measurements of the first- and second-order azimuthal anisotropic parameters, v1 and v2, of light nuclei (d, t, 3He, 4He) produced in sNN = 3 GeV Au+Au collisions at the STAR experiment. An atomic mass number scaling is found in the measured v1 slopes of light nuclei at mid-rapidity. For the measured v2 magnitude, a strong rapidity dependence is observed. Unlike v2 at higher collision energies, the v2 values at mid-rapidity for all light nuclei are negative and no scaling is observed with the atomic mass number. Calculations by the Jet AA Microscopic Transport Model (JAM), with baryonic mean-field plus nucleon coalescence, are in good agreement with our observations, implying baryonic interactions dominate the collective dynamics in 3 GeV Au+Au collisions at RHIC. © 2022 The Author
13 citations (Crossref) [2023-10-31] tex.art_number: 136941 tex.coden: PYLBA tex.document_type: Article tex.source: Scopus
Keywords: dept.phy; peer-reviewed

Measurement of cold nuclear matter effects for inclusive J/ψ in p+Au collisions at sNN=200 GeV - STAR Collaboration (Physics Letters, Section B: Nuclear, Elementary Particle and High-Energy Physics, 2022)
Measurement by the STAR experiment at RHIC of the cold nuclear matter (CNM) effects experienced by inclusive J/ψ at mid-rapidity in 0-100% p+Au collisions at sNN = 200 GeV is presented. Such effects are quantified utilizing the nuclear modification factor, RpAu, obtained by taking a ratio of J/ψ yield in p+Au collisions to that in p+p collisions scaled by the number of binary nucleon-nucleon collisions. The differential J/ψ yield in both p+p and p+Au collisions is measured through the dimuon decay channel, taking advantage of the trigger capability provided by the Muon Telescope Detector in the RHIC 2015 run. Consequently, the J/ψ RpAu is derived within the transverse momentum (pT) range of 0 to 10 GeV/c. A suppression of approximately 30% is observed for pT<2 GeV/c, while J/ψ RpAu becomes compatible with unity for pT greater than 3 GeV/c, indicating the J/ψ yield is minimally affected by the CNM effects at high pT. Comparison to a similar measurement from 0-20% central Au+Au collisions reveals that the observed strong J/ψ suppression above 3 GeV/c is mostly due to the hot medium effects, providing strong evidence for the formation of the quark-gluon plasma in these collisions. Several model calculations show qualitative agreement with the measured J/ψ RpAu, while their agreement with the J/ψ yields in p+p and p+Au collisions is worse. © 2022 The Author(s)
5 citations (Crossref) [2023-10-31] tex.art_number: 136865 tex.author_keywords: Cold nuclear matter effects; J/ψ suppression; RHIC tex.coden: PYLBA tex.document_type: Article tex.source: Scopus
Keywords: dept.phy; peer-reviewed

Measurement of inclusive electrons from open heavy-flavor hadron decays in p+p collisions at s =200 GeV with the STAR detector - STAR Collaboration (Physical Review D, 2022)
We report a new measurement of the production cross section for inclusive electrons from open heavy-flavor hadron decays as a function of transverse momentum (pT) at midrapidity (|y|¡0.7) in p+p collisions at s=200 GeV. The result is presented for 2.5¡pT¡10 GeV/c with an improved precision above 6 GeV/c with respect to the previous measurements, providing more constraints on perturbative QCD calculations. Moreover, this measurement also provides a high-precision reference for measurements of nuclear modification factors for inclusive electrons from open-charm and -bottom hadron decays in heavy-ion collisions. © 2022 American Physical Society.
2 citations (Crossref) [2023-10-31] tex.art_number: 032007 tex.document_type: Article tex.source: Scopus
Keywords: dept.phy; peer-reviewed

Investigation of experimental observables in search of the chiral magnetic effect in heavy-ion collisions in the STAR experiment - Choudhury, S.; Dong, X.; Drachenberg, J. L.; Dunlop, J. C.; Esumi, ShinIchi; Feng, Yicheng; Finch, E.; Hu, Yu; Jia, Jiangyong; Lauret, Jerome; Li, Wei; Liao, Jinfeng; et al. (Chinese Physics C, 2022)
The chiral magnetic effect (CME) is a novel transport phenomenon, arising from the interplay between quantum anomalies and strong magnetic fields in chiral systems. In high-energy nuclear collisions, the CME may survive the expansion of the quark-gluon plasma fireball and be detected in experiments. Over the past two decades, experimental searches for the CME have attracted extensive interest at the Relativistic Heavy Ion Collider (RHIC) and the Large Hadron Collider (LHC). The main goal of this study is to investigate three pertinent experimental approaches: the correlator, the R correlator, and the signed balance functions. We exploit simple Monte Carlo simulations and a realistic event generator (EBE-AVFD) to verify the equivalence of the core components among these methods and to ascertain their sensitivities to the CME signal and the background contributions for the isobar collisions at the RHIC. © 2022 Chinese Physical Society and the Institute of High Energy Physics of the Chinese Academy of Sciences and the Institute of Modern Physics of the Chinese Academy of Sciences and IOP Publishing Ltd.
11 citations (Crossref) [2023-10-31] https://iopscience.iop.org/article/10.1088/1674-1137/ac2a1f ; http://hepnp.ihep.ac.cn/article/id/55afc331-6758-45b3-97ce-444828b72c70 ; http://cpc.ihep.ac.cn/article/doi/10.1088/1674-1137/ac2a1f ; http://csnsdoc.ihep.ac.cn/article/doi/10.1088/1674-1137/ac2a1f ; https://inspirehep.net/literature/1863127
Keywords: dept.phy; peer-reviewed